Investigating the mechanism of ADP-forming acetyl-CoA synthetase from the protozoan parasite Entamoeba histolytica - Jones, Cheryl P. (FEBS Lett, 2017)
ADP-forming acetyl-CoA synthetase (ACD) catalyzes the interconversion of acetyl-CoA and acetate. The related succinyl-CoA synthetase follows a three-step mechanism involving a single phosphoenzyme, but a novel four-step mechanism with two phosphoenzyme intermediates was proposed for Pyrococcus ACD. Characterization of enzyme variants of Entamoeba ACD in which the two proposed phosphorylated His residues were individually altered revealed that only His252 is essential for enzymatic activity. Analysis of variants altered at two residues proposed to interact with the phosphohistidine loop that swings between distinct parts of the active site are consistent with a mechanism involving a single phosphoenzyme intermediate. Our results suggest ACDs with different subunit structures may employ slightly different mechanisms to bridge the span between active sites I and II.